THE POSITIONING MATTERS OF THE DOLL’S HOUSE IN POSTCOLONIALISM - Dwi Mega Fitriana (Universitas PGRI Madiun, 2015)
The purpose of this research is to analyze the self-positioning and social class phenomenon of The Doll’s House. It tells about social oppression create by upper to dominate lower class. Upper class takes part as dominant while lower class takes part as minority in society. This research uses qualitative research. The researcher needs postcolonial theory to identify the self-positioning between upper and lower class in the short story. The analysis reveals that upper class treats lower class to be the other, subaltern and create social discrimination. The conclusion is the upper class founds powerful, otherwise the lower class is found surviving not fighting from injustice.